Understanding continuance usage intention of mHealth in a developing country: An empirical investigation. Issue 2 (23rd March 2020) - Kaium, Md Abdul; Bao, Yukun; Alam, Mohammad Zahedul; Hoque, Md. Rakibul
Abstract : Purpose: This study aims to understand the factors affecting the continuance usage intention (CUI) of mHealth among the rural elderly. Design/methodology/approach: An integrated model was proposed with the constructs derived from multiple models such as the unified theory of acceptance and use of technology, information system success model and expectation confirmation model. Data were collected from 400 participants who had prior experiences with mHealth services in Bangladesh. The research model was tested using the partial least squares method based upon structural equation modelling. Findings: The findings indicated that system quality, performance expectancy, facilitating conditions and social influence were significant to the degree of confirmation and ultimately affect satisfaction and CUI. Surprisingly, service quality and information quality were insignificant. Research limitations/implications: This study has added in the field of knowledge by contributing some new thoughts and interpretations of continuance usage modelling for mHealth services. The findings may become beneficial for the government agencies, policymakers, mHealth systems developers and service providers. Originality/value: As limited research was found on CUI of mHealth in the integrated view of rural elderly's value, this research contributes to the extant literature by categorizing key factors that might support to proliferate the continuance usage of this service. Moreover, the contextualization of the related variables and integration of the existing model is theoretically original. Furthermore, because of a generic approach, the findings could be easily modified to assist other developing countries in the planning and up-take of mHealth.